Current Concepts of Biliary Atresia and Matrix Metalloproteinase-7: A Review of Literature - Nomden, Mark; Beljaars, Leonie; Verkade, Henkjan J.; Hulscher, Jan B. F.; Olinga, Peter (Frontiers in Medicine, 2020)
Biliary atresia (BA) is a rare cholangiopathy of infancy in which the bile ducts obliterate, leading to profound cholestasis and liver fibrosis. BA is hypothesised to be caused by a viral insult that leads to over-activation of the immune system. Patients with BA are surgically treated with a Kasai portoenterostomy (KPE), which aims to restore bile flow from the liver to the intestines. After KPE, progressive liver fibrosis is often observed in BA patients, even despite surgical success and clearance of their jaundice. The innate immune response is involved during the initial damage to the cholangiocytes and further differentiation of the adaptive immune response into a T-helper 1 cell (Th1) response. Multiple studies have shown that there is continuing elevation of involved cytokines that can lead to the progressive liver fibrosis. However, the mechanism by which the progressive injury occurs is not fully elucidated. Recently, matrix metalloproteinase-7 (MMP-7) has been investigated to be used as a biomarker to diagnose BA. MMPs are involved in extracellular matrix (ECM) turnover, but also have non-ECM related functions. The role of MMP-7 and other MMPs in liver fibrosis is just starting to be elucidated. Multiple studies have shown that serum MMP-7 measurements are able to accurately diagnose BA in a cohort of cholestatic patients while hepatic MMP-7 expression correlated with BA-related liver fibrosis. While the mechanism by which MMP-7 can be involved in the pathophysiology of BA is unclear, MMP-7 has been investigated in other fibrotic pathologies such as renal and idiopathic pulmonary fibrosis. MMP-7 is involved in Wnt/β-catenin signaling, reducing cell-to-cell contact by shedding of E-cadherin, amplifying inflammation and fibrosis via osteopontin (OPN) and TNF-α. This review aims to describe the current understandings of the pathophysiology of BA. Subsequently, we describe how MMP-7 is involved in other pathologies, such as renal and pulmonary fibrosis. Then, we propose how MMP-7 can potentially be involved in BA. By doing this, we aim to describe the putative role of MMP-7 as a prognostic biomarker in BA and to provide possible new therapeutic and research targets that can be investigated in the future.